Virtual teaching, a global educational need - Artemio Oyarce-Mariñas, Víctor; Morales Chicana, Eleodoro; Pedro Solís-Trujillo II , Beymar (Seven Editora, 2023)
With the arrival of COVID-19, the world suffered unexpected impacts. It forced countries to make accelerated changes in different aspects; of course, education was affected too. On this latter point, UNESCO reveals that approximately 94% of students in the world were harmed by the suspension of face-to-face classes. To counteract the effect of this conjuncture, the education sector implemented virtual teaching through existing technological tools. The speed with which the educational system had to adapt to this modality raised questions about the management and functionality of virtuality in education. The purpose of this document is to analyze the need of adopting virtual teaching with the change of pedagogical strategies and to evaluate the digital skills that teachers need to adapt to virtual education, taking advantage of technological resources for the motivation of the student and their access to education. The descriptive method of documentary type and the analysis of the contents were used to process the information. Finally, we conclude on the importance of teaching work that, with a positive attitude towards technology, this has to rethink its role as a facilitator of the educational process and the fundamentals of the appropriation of digital tools. DOI: 10.56238/pacfdnsv1-021